Recommended Procedures for Damage-Based Serviceability Design of Steel Buildings under Wind Loads - Aswegan, Kevin; Charney, Finley A.; Jarrett, Jordan (Engineering Journal, 2015)
This paper provides a recommended procedure for nonstructural damage control of steel buildings under serviceability-level wind loads. Unlike traditional procedures that provide a single drift limit under a given reference load, the recommended procedure provides a decision space that spans a range of wind hazards and associated damage states. Central to the procedure are the use of shear strain in nonstructural components as the engineering demand parameter and the use of component fragility as a reference for limiting damage